Psychosocial and behavioural prognostic factors for diabetic foot ulcer development and healing: a systematic review. Issue 8 (17th June 2020) - Westby, M.; Norman, G.; Vedhara, K.; Game, F.; Cullum, N.
Abstract: Aim: To investigate whether ulceration, amputation and healing of foot ulcers in people living with diabetes are associated with psychosocial and behavioural factors. Methods: We searched MEDLINE, Embase, PsychINFO, CINAHL and The Cochrane Library to March 2019 for longitudinal studies with multivariable analyses investigating independent associations. Two reviewers extracted data and assessed risk of bias. Results: We identified 15 eligible studies involving over 12 000 participants. Clinical and methodological heterogeneity precluded meta‐analysis, so we summarize narratively. Risk of bias was moderate or high. For ulceration, we found significantly different results for people with and without an ulcer history. For those with no ulcer history, moderate quality evidence suggests depression increases ulcer risk [three studies; e.g. hazard ratio (HR) 1.68 (1.20, 2.35) per Hospital Anxiety and Depression Scale (HADS) standard unit]. Better foot self‐care behaviour reduces ulcer risk [HR 0.61 (0.40, 0.93) per Summary of Diabetes Self‐Care Activities scale standard unit; one study]. For people with diabetes and previous ulcers, low‐ or very low‐quality evidence suggests little discernible association between ulcer recurrence and depression [e.g. HR 0.88 (0.61, 1.27) per HADS standard unit], foot self‐care, footwear adherence or exercise. Low‐quality evidence suggests incomplete clinic attendance is strongly associated with amputation [odds ratio (OR) 3.84 (1.54, 9.52); one study]. Evidence for the effects of other psychosocial or behavioural factors on ulcer healing and amputation is very low quality and inconclusive. Conclusions: Psychosocial and behavioural factors may influence the development of first ulcers. More high quality research is needed on ulcer recurrence and healing. (Open Science Framework Registration: https://osf.io/ej689 ) What's new?: What's known: Self‐management influences both ulceration and healing in people living with diabetes. Intervention adherence could prevent up to 75% of foot ulcers. This study found that: In people without previous ulcers, moderate quality evidence suggests both depression and poorer foot self‐care increase the risk of ulceration. In people with previous ulcers, low‐/very low‐quality evidence suggests little association between psychosocial/behavioural factors and ulceration. Evidence on ulcer healing is inconclusive. Further research is needed. Clinical implications: Depression and poor foot self‐care may increase ulceration risk in people living with diabetes with no ulceration history.